DETERMINANTS OF COAL EXIT STRATEGY IN THE BANKING INDUSTRY - JAMET, Benoît; BOUSQUET, Julien; MASSÉ, Antoine (Bankers, Markets & Investors, 2023)
In recent years, an increasing number of major international banks have begun to announce their exit from the coal sector, in response to the trend initiated by public actors such as governments and related public sector financial institutions. This article examines the determinants of coal exit strategies of international banks. Using a sample of 111 banks from 31 countries and a PLSPM methodology, the results show that: 1) the announced strategies are particularly partial in nature and the financing allocated to coal firms is still high, 2) external variables (i.e., national and institutional contexts) significantly influence exit scores, notably coal dependence, progress in the energy transition and the environmental performance of the home countries, 3) with the exception of size, internal variables (e.g., exposure to the sector, risk and profitability) have no impact on coal exit scores. Banks therefore adopt a defensive strategy: the managerial decision echoes national energy and environmental policies, which underlines the crucial political and regulatory role of governments in influencing bank strategies.